FLUKTUASI EKSPOR KOPI INDONESIA KE JERMAN TAHUN 2010-2014 - Sari, Mutiara; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Coffee is an important commodity and the third most popular beverage ingredient inthe World after Water and Tea.This causes Coffee consumption at the world to increase everyyear. Therefore the demand for coffee from consumer countries is also increasing like Americaand Germany.Coffee consumption levels in Germany are very high over 86% of Germans drinkcoffee every day. Germany cooperates with coffee exporting countries such as Brazil andIndonesia for meet domestic demand.Indonesian coffee exports to Germany in 2010-2014 havefluctuated, where the lowest number in 2011 amounted to 27 tons and the highest figure in 2010was 63 tons.The research used qualitative research method with analytical descriptivecharacteristic. The observational data in the analysis consisted of 5 factors: domestic coffeeprice, world coffee price, coffee consumption level, GDP per capita, and rupia exchange rateagainst dollar. Further dikonfersi dollar unity, so it can be made comparisons to determinewhich factors are most influential on fluctuations of Indonesian coffee exports to Germany in2010-2014.The results of this study indicate that the five factors, Coffee Consumption Level Mostinfluential on Indonesian coffee exports to Germany in 2010-2014 with drinking coffee cultureindicators in Germany has become a tradition since the 7th abab and German demographicsaverage age above 17 years and under 50 years, as well as retail segmentation to get coffee.Key word: Coffee, Consumption, Fluctuation